2021
DOI: 10.1186/s12885-021-08701-y
|View full text |Cite|
|
Sign up to set email alerts
|

Attention to principles of exercise training: an updated systematic review of randomized controlled trials in cancers other than breast and prostate

Abstract: Background The primary objective of this systematic review was to update our previous review on randomized controlled trials (RCTs) of exercise in cancers other than breast or prostate, evaluating: 1) the application of principles of exercise training within the exercise prescription; 2) reporting of the exercise prescription components (i.e., frequency, intensity, time, and type (FITT)); and 3) reporting of participant adherence to FITT. A secondary objective was to examine whether reporting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 151 publications
1
27
0
Order By: Relevance
“…Incomplete reporting of FITT prescription components is a persistent problem in exercise oncology. The findings from this review were consistent with a recent systematic review of exercise interventions where only 58% of studies reported all FITT prescription components (Bland et al, 2021). Operationalizing exercise prescriptions using FITT components is needed to allow comparison across interventions and improve intervention designs (Fairman et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Incomplete reporting of FITT prescription components is a persistent problem in exercise oncology. The findings from this review were consistent with a recent systematic review of exercise interventions where only 58% of studies reported all FITT prescription components (Bland et al, 2021). Operationalizing exercise prescriptions using FITT components is needed to allow comparison across interventions and improve intervention designs (Fairman et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Adherence is frequently associated with other concepts such as attendance or compliance to the prescribed exercise program (Collado-Mateo et al, 2021) because there is no consensus on the definition of adherence to exercise interventions in the literature (Hawley-Hague et al, 2016). Bland et al (2021) suggest a comprehensive method for reporting exercise adherence is to describe the frequency, intensity, time, and type (FITT) of the prescription. Frequency refers to the number of sessions per week; intensity to the level of exertion; time to the duration of exercise sessions; and type to the type of exercise, such as aerobic or resistance training.…”
mentioning
confidence: 99%
“…The clinician is now uncertain what the ‘effective’ exercise programme was. The same could be said for clinicians working in exercise oncology, where key principles of training (eg, progression and reversibility) and prescriptive components of exercise (eg, frequency, intensity, time and type) are poorly reported 21…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified the following typesetting errors: A small number of references were not inserted in-text correctly. As a result, some in-text citations are not correct for specific statements in our results section on pages 4-5.…”
mentioning
confidence: 99%
“…Please see below for the corrected Table 2 . The reference list has been corrected in the updated article [ 1 ].…”
mentioning
confidence: 99%